2014
DOI: 10.1017/s1755267214000840
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and comments on the benthic foraminiferal assemblage observed around the mineral submarine spring in Kuşadası (Aydın, Turkey)

Abstract: Opinions and comments on the benthic foraminiferal assemblage observed around the mineral submarine spring in Kuşadası (Aydın, Turkey) mehmet baki yokes 1 , engin meric ‚ 2 , niyazi avs ‚ar 3 , i ‹pek barut 4 , seyfettin tas 4 , mustafa eryilmaz 5 , feyza dinc ‚er 6 and cu ¤ neyt bircan 7The aim of the study was to investigate the benthic foraminiferal fauna around the mineral water spring in Pamucak Cove, north-west Kuşadası (Aydın) and figure out the effects of the spring on the fauna. The spring was located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Alterations in the ecological conditions have been found to be the main reason causing these kinds of morphological abnormalities. Besides the studies performed by researchers from various countries, in our previous studies also we have shown that extreme salinity, rapid changes in salinity, presence of heavy metals and trace elements, both thermal and cold water submarine springs and the chemical compositions of the submarine spring waters in karstic regions are suggested to be the main factors which cause changes ecological conditions (Nigam et al, 2006;Meriç et al, 2003aMeriç et al, , b, 2009aMeriç et al, , b, c, 2010Meriç et al, , 2012aOkuş et al, 2004Okuş et al, , 2010Yokeş et al, 2014;Simav, et al, 2015Gazioğlu, 2018;Duman et al, 2019).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Alterations in the ecological conditions have been found to be the main reason causing these kinds of morphological abnormalities. Besides the studies performed by researchers from various countries, in our previous studies also we have shown that extreme salinity, rapid changes in salinity, presence of heavy metals and trace elements, both thermal and cold water submarine springs and the chemical compositions of the submarine spring waters in karstic regions are suggested to be the main factors which cause changes ecological conditions (Nigam et al, 2006;Meriç et al, 2003aMeriç et al, , b, 2009aMeriç et al, , b, c, 2010Meriç et al, , 2012aOkuş et al, 2004Okuş et al, , 2010Yokeş et al, 2014;Simav, et al, 2015Gazioğlu, 2018;Duman et al, 2019).…”
Section: Introductionmentioning
confidence: 77%
“…Total alpha values are ranging between 0.50±5.07(6)-4.57±27.23 (5) Bq/l, whereas total beta values are found to be 2. 29±5.11 (2)-22.19±26.61 (1) Bq/l (Yokeş et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When total alfa and beta countings of the springs in the study area are correlated with other hot springs located in Çeşme-Ilıca in northwest and the Kuşadası Bay in south, sea water samples of the Çeşme-Ilıca show resemblance with other hot springs in this area (Yenal et al, 1975;Meriç et al, 2012a). However, the total alfa and beta countings of hot springs in the Kuşadası Bay (Güzelçamlı, Kemerli, Kuşadası Kaynağı, Doğanbey, Karakoç, Cumali) are in different values (Yokeş et al, 2014).…”
Section: Discussion and Resultsmentioning
confidence: 99%